Representing the family - Chambers, Deborah, 1954- (SAGE, 2001)
Looking at how the family is represented by the media, and by scrutinizing the manner in which it is regulated, this book uncovers the ways in which academic research and welfare policy have colluded with political rhetoric and the popular media to re-invent a mythical ideal family.